2008
DOI: 10.1111/j.1540-5907.2008.00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement without Peace? International Mediation and Time Inconsistency Problems

Abstract: Mediation has competing short-and long-term A cursory glance at the diplomatic realm of international politics would suggest that mediation is an important element in the resolution of international conflict. Nobel Peace Prizes are awarded for successful efforts, and national leaders offer their services with considerable fanfare. Seasoned diplomats have contributed numerous essays and books on the subject. Yet mediation is rarely given much attention in the general literatures on international conflict. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
193
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(204 citation statements)
references
References 57 publications
7
193
0
4
Order By: Relevance
“…Belligerents can struggle to credibility communicate peaceful intentions, in particular regarding commitment to agreements (Fearon, 1995;Walter, 1997). When the incentives for cooperation are expected to change over time, it is challenging for the potential beneficiary to guarantee that they will not renege in the future (Beardsley, 2008). The incentives that each actor may have to later renege on any agreement can, in the same way as they can lead to the onset of conflict, also prevent the resolution of war (Beardsley et al, 2006;Wilkenfeld et al, 2005).…”
Section: Bargaining Failure In Civil Warmentioning
confidence: 99%
“…Belligerents can struggle to credibility communicate peaceful intentions, in particular regarding commitment to agreements (Fearon, 1995;Walter, 1997). When the incentives for cooperation are expected to change over time, it is challenging for the potential beneficiary to guarantee that they will not renege in the future (Beardsley, 2008). The incentives that each actor may have to later renege on any agreement can, in the same way as they can lead to the onset of conflict, also prevent the resolution of war (Beardsley et al, 2006;Wilkenfeld et al, 2005).…”
Section: Bargaining Failure In Civil Warmentioning
confidence: 99%
“…The creation of a peace settlement does not always imply an end to violence, nor does it guarantee that a conflict will not reoccur. Recent research has suggested that even though mediation can help actors identify acceptable outcomes, the artificial incentives created by mediation often result in less durable agreements than bilateral settlements (Beardsley, 2008;. Still, to reach a peace settlement is a notable step towards peace and conflict resolution, and a significant achievement for a third-party mediator (see Bercovitch, 2007;DeRouen, Bercovitch & Pospieszna, 2011;Jackson, 2000;Touval & Zartman, 1985), so we see this as a valid indicator for at least one dimension of mediation success.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…A great deal of research has focused on developing propositions on when mediation is most likely as well as when it can help decrease the risk of further violence or escalation (Beardsley, 2008(Beardsley, , 2009(Beardsley, , 2010Regan, 2010;Svensson, 2007Svensson, , 2009). However, most research on mediation so far has exclusively evaluated hypotheses on mediation on observed (insample) data, and not considered to what extent existing research provides us with a basis for predicting the likelihood or outcome of mediation out-of-sample.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies that have considered how third-party conflict management can affect the duration of peace after conflict indicate that heavy-handed involvement might do well in producing immediate results but can also weaken the ability for the disputants to reach a self-enforcing peace (Beardsley 2008(Beardsley , 2011aBetts 2001;Kuperman 2001;Luttwak 2001;Rauchhaus 2009;Werner and Yuen 2005). Related, Greig and Diehl (2005) posit that peacekeepers decrease the incentives for disputants to fully settle their grievances.…”
Section: Overcommitment Of Leveragementioning
confidence: 99%
“…Extant studies that have assessed how third-party involvement during conflict affects the duration of peace have focused primarily on mediation (Beardsley 2008(Beardsley , 2011aGartner and Bercovitch 2006). Diehl, Reifschneider and Hensel (1996) is a notable study that has considered whether UN involvement of various types during crises can increase post-crisis stability, but their results are for the most part indeterminate and are specific to the interstate context.…”
mentioning
confidence: 99%